The IMPACT OF BANK RESTRUCTURING ANNOUNCEMENT ON THE BANKING STOCK PRICES: The Cases of Indonesia’s Banking Reforms on March 13, 1999, and The Issuance of Government Bonds on May 28, 1999 - Muhammad Fendi Susiyanto (Gadjah Mada International Journal of Business, 2018)
This study is an event study that aims to investigate how successful the banking reforms measures that has already been done by the Indonesian government in order to strengthen its banking system. There were two events to be investigated in this study, first (1) The banking reforms announcement on March 13, 1999 which consists of the closure of 38 private banks, the taken-over of 7 private banks, 9 private banks will be recapitalized, and let 73 private banks to continue their operation without joining the recapitalization program; second (2) on May 28, 1999 Minister of Finance issued government bonds amounted to Rp 103,831 trillion to complete the private banks’ recapitalization, and also issued the other government bonds to repay the obligations of frozen commercial banks’ and rural banks’ regarding its liquidity support, to Bank Indonesia amounted to Rp 53,779 trillion.These two events above, are expected to be good news or favorable information for investors on the Jakarta Stock Exchange (JSX), and should be responded positively by investors which indicates significantly increases on banking stocks after the event dates.Thirteen samples of banking stocks which were listed on the Jakarta Stock Exchange (JSX) at the beginning of 1997 were used to investigate the reaction of banking stocks around the dates of these two events. By using the paired-samples mean difference test, we did not find significant differences between abnormal returns before and after the event dates. Furthermore, the cumulative abnormal return of banking stocks around the banking reforms announcement on March 13, 1999 and the issuance of government bonds announcement on May 28, 1999 were decreasing gradually until it reached the negative area. Trading Volume Activity (TVA) test, on the banking stock volume around the banking reforms announcement on March 13, 1999 has found that TVA of banking stocks after the event date was significantly greater than TVA of banking stocks before the event date. The result was not found on the issuance of government bonds event.In general, from these results, it can be concluded that the banking reforms measures done by the government was not successfully implemented from the market’s point of view.The abnormal return tests have been conducted, yet it is still found a significant abnormal return around both the banking reforms announcement on March 13, 1999 and the issuance of government bonds announcement on May 28, 1999. These findings did not support the semi-strong efficiency of the Jakarta Stock Exchange (JSX).